Pacific Chemicals Bhd (Business times (Kuala Lumpur, Malaysia), 1997)
PACIFIC Chemicals Bhd announced a 19 per cent drop in group pre-tax profit to RM39.48 million with a 3 per cent increase in turnover to RM141.97 million for the year ended December 31 1996.